Interactive effects of Rhizobacteria for Managing Spodoptera exigua on Shallot Plants (Allium cepa Linnaeus) under Field Conditions - Hidrayani Hidrayani; Nurbailis Nurbailis; Fitri Yeni; Zahlul Ikhsan (Jurnal Proteksi Tanaman)
Spodoptera exigua is the primary pest attacking shallot plants from the vegetative to the generative phase. Yield loss caused by S. exigua attack can reach 57%. Rhizobacteria have been known to be used as biocontrol agents for controlling insect pests. The research objectives were to determine and compare the effectiveness of Yuyaos and BPTPH rhizobacteria formula (Bacillus sp.) in suppressing the attack of S. exigua on shallot-growing areas. The study used a completely randomized design (CRD) of 3 treatments and five replications. The treatment consisted of shallot seedlings treated with two types of rhizobacteria (Yuyaos and BPTPH) and water (without rhizobacteria) as control before planting. Beneficial effects of the rhizobacteria on shallot plants were observed in the following variables, including the development of the S. exigua population, damage level of S. exigua, and shallot growth. The results showed that introducing Yuyaos rhizobacteria (RZ2.1AG1, Bacillus thuringiensis), which originated from the rhizosphere of the chili plant, was the best way to protect shallot plants from S.exigua. Effectively reduced the population of S.exigua (78.90%), leaf damage (62.12%), and damage intensity (38.88%). On the other hand, Yuyaos was also influential in increasing tuber growth (11.11%), plant height (43.29%), number of leaves (58.33%), and number of tillers (22.22%).